Dealing with Systemic Sovereign Debt Crises: Fiscal Consolidation, Bail-Ins, or Bail-Outs?. Issue Volume 66:Issues 4(2018) (December 2018) - Sandri, Damiano
Abstract The paper presents a tractable model to understand how international financial institutions (IFIs) should deal with the sovereign debt crisis of a systemic country, in which case private creditors' bail-ins entail international spillovers. We use the model to solve for the optimal combination between fiscal consolidation, bail-ins, and bail-outs to restore debt sustainability. For non-systemic countries, only fiscal consolidation and bail-ins should be used, based on an ex-post assessment of their relative costs. Systemic crises raise significant new challenges. First, to reduce the spillovers associated with bail-ins, IFIs should be able to provide bail-outs. Second, to contain the moral hazard effects of bail-outs, IFIs should operate under a binding crisis-resolution framework that limits the provision of bail-outs to highly systemic countries, coupled with more stringent fiscal consolidation requirements.